PERLINDUNGAN HUKUM BAGI KARYAWAN ALFAMART SEBAGAI SAKSI PENCURIAN BARANG - Bima Meidianto Nugraha; Hari Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The journal entitled "Legal Protection of Alfamart employees as witnesses" describes employment problems that arise as a result of technological advances in the modern era, one of which is caused by the digitalization of the circulation of video in problems. The purpose of this paper is to find out how the law regulates the rights and legal protection of workers who are threatened with acts of defamation. The research method used is the normative legal research method. This research method is normative by looking at the law from an internal perspective whose object of research is to use legal norms where there is still a vagueness of norms in legal protection due to the impact of this digitalization. 1945 Constitution article 27 paragraph 2, and in article 67 paragraph 1 and 2 contained in Law Number 13 of 2003 concerning Manpower. The definition of Employment Law is a written law that has been codified in the Civil Code and partly (possibly more than that has been codified). Manpower Law is essentially a set of rules governing before and until the end of the employment relationship between the worker and the company where the worker works. In other words, Employment Law has the scope of Legal Protection from the beginning before entering the World of Work until the end of the Employment Relationship itself. Legal protection has an important role for all society, the existence of legal protection is one of the spaces to get justice and carry out a process of action to achieve the truth of the facts. Legal protection is made with the aim of providing justice regarding someone's actions if something is unwanted and getting sanctions in accordance with the regulations that have been made